PENGARUH KOMPETENSI MASINIS TERHADAP KESELAMATAN PERJALANAN KERETA API MRT JAKARTA - Artha Wiguna Yudistira; Sudarwati (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
Since actively operating to transport passengers, MRT Jakarta trains have experiencedemergencies or technical difficulties, namely a strike due to a power outage in August2019. The MRT Operation Control Center (OCC) team detected that four (4) trains hadstopped between underground stations. The MRT strike made dozens of passengersstraight away evacuated from the inside to the outside of the train to the station platform.This evacuation is led by a machinist and a team of security officers and carried out onfoot through the emergency lane (emergency walkways). Therefore in the operation ofthis electric train, it is necessary Reliable and competent human resources to be able tocarry out their duties and responsibilities he answered, for example the Railway FacilitiesCrew (ASP). The purpose of this research is to determine the effect of machinistcompetence on the safety of MRT train travel Jakarta which consists of skills, knowledgeand attitude. The method used is analysis descriptive with a quantitative approach andusing simple and regression analysis techniques multiple regression assisted by the SPSSprogram. Data collection using the method observation, distribution of questionnaires,and documents. Data processing using editing, scaling measurements, tabulation. Theresults of this study are that there is a significant influence of skills engineer on the safetyof train travel by 25.4%. There is influence machinist's significant knowledge of the safetyof train travel by 20.2%. There is a significant influence of the driver's attitude on thesafety of train travel fire of 37.6%.. There is a significant influence of skill, knowledgeand attitude of the machinist together on the safety of train travel by 52.7%.